2002
DOI: 10.1152/physiolgenomics.00011.2002
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression changes during mouse skeletal myoblast differentiation revealed by transcriptional profiling

Abstract: -Studies described here utilize high-density oligonucleotide arrays to characterize changes in global mRNA expression patterns during proliferation, cell cycle withdrawal, and terminal differentiation in mouse C2C12 myoblasts. Statistical analyses revealed 629 sequences differentially regulated between proliferating and differentiating myoblasts. These genes were clustered using self-organizing maps to identify sets of coregulated genes and were assigned to functional categories that were analyzed for distribu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
74
0
2

Year Published

2003
2003
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(92 citation statements)
references
References 41 publications
16
74
0
2
Order By: Relevance
“…Our microarray data on RR/KI-mTOR C2C12 cells differentiating under normal conditions generally agreed with the previous report, even though a complete overlap was not expected because of the different experimental conditions and different coverage of the genome, our chip was a 15,000 cDNA array and theirs an unrelated 11,000 oligo array (32). Our microarray analysis was aimed at gathering more specific information: the comparison of RR/KI- mTOR cells differentiating in the absence and presence of rapamycin revealed potential targets of mTOR kinase-dependent signaling during myocyte differentiation and maturation, and furthermore, the data contributed to our general understanding of the gene expression programs specifically underlying myotube maturation.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Our microarray data on RR/KI-mTOR C2C12 cells differentiating under normal conditions generally agreed with the previous report, even though a complete overlap was not expected because of the different experimental conditions and different coverage of the genome, our chip was a 15,000 cDNA array and theirs an unrelated 11,000 oligo array (32). Our microarray analysis was aimed at gathering more specific information: the comparison of RR/KI- mTOR cells differentiating in the absence and presence of rapamycin revealed potential targets of mTOR kinase-dependent signaling during myocyte differentiation and maturation, and furthermore, the data contributed to our general understanding of the gene expression programs specifically underlying myotube maturation.…”
Section: Discussionsupporting
confidence: 89%
“…Gene profiling comparing myoblast and myotube stages of C2C12 cells was reported previously (32). Our microarray data on RR/KI-mTOR C2C12 cells differentiating under normal conditions generally agreed with the previous report, even though a complete overlap was not expected because of the different experimental conditions and different coverage of the genome, our chip was a 15,000 cDNA array and theirs an unrelated 11,000 oligo array (32).…”
Section: Discussionsupporting
confidence: 89%
“…We analyzed cells that were growing, in the process of differentiation (24 h in DM), or fully differentiated into myotubes. Globally, our results agree with data obtained previously (Moran et al 2002).…”
Section: Linking Expression With Promoter Occupancy By Mrfssupporting
confidence: 93%
“…Beyond these first steps, our knowledge is somewhat fragmentary: Relatively few physiological targets of MRFs and MEF2 have been identified, and the number of genes known to be regulated by these factors is considerably smaller than the number of genes induced upon myogenic differentiation (Moran et al 2002). In addition, the role of MyoD in myogenic differentiation appears to be considerably more complex, since recent studies point to a role for this factor in transcriptional repression as well as activation (Mal and Harter 2003).…”
mentioning
confidence: 99%
“…5) Shen et al have focused on the events taking place during C2C12 myoblast cell cycle withdrawal. 6) Tomczak et al reported the analysis of 24,290 murine probe sets in a 12-d time course of differentiating C2C12 myoblasts.…”
Section: -7)mentioning
confidence: 99%